The importance of resource allocation for the interplay between automatic and cognitive control in response inhibition – An EEG source localization study. (October 2022) - Ghin, Filippo; Stock, Ann-Kathrin; Beste, Christian
Abstract: Goal-directed behavior often requires the inhibition of prepotent automatic responses. Response inhibition encompasses several top-down cognitive operations embedded in a neural network extending from fronto-cortical regions to subcortical nuclei. Yet, it has remained unclear whether the early allocation of cognitive resources also modulates response inhibition performance and neural structures involved in this process. To investigate this question, we used a Simon Nogo task, which was designed to manipulate the relationship between automaticity and cognitive control during response inhibition, and combined it with an electroencephalogram (EEG) and source localization approach. We showed that the early allocation of cognitive resources, as reflected by the P2 amplitude, might be a critical determinant in the interplay between automaticity and cognitive control in response inhibition. Specifically, the obtained results demonstrated that individual variations in cognitive resource allocation modulated the need for conflict monitoring and engagement in cognitive control processes, as reflected by N2 and P3b amplitudes, respectively. Importantly, larger P2 amplitudes were associated with higher activation in cortical regions encompassing the temporo-parietal junction (TPJ). This stresses the importance of this cortical region for the encoding of relevant stimulus information to resolve conflicting contexts in response inhibition. The increased cognitive control in more automatic contexts was also reflected by higher activation of the superior and medial frontal cortices. These findings provide a new perspective on response inhibition, suggesting that early resource allocation is a central modulator of the interaction between automaticity and cognitive control.